Stickers: a exibição das imagens entre o urbano e o virtual - Bornhausen, Diogo Andrade (2011)
This research aims at investigating the sticker phenomenon in its varied communicational stances. As an image whose primary purpose is to visually intervene in the urban space, stickers are the outcome of an image-engendering process whose very images precede the emergence of stickers and have always intended to maximize their reach by means of a massive reproducibility. But stickers go beyond the urban domain and onto the Internet, which is used for further publicizing, promotional purposes. Faced with this evidence, we aim at understanding the reasons why stickers happen to move across these different milieus, and understanding the eventual modifications they might go through from the very beginning of their action. Having said that, our hypothesis is that, since it appears as an alternative to the visibility crisis of the preceding images, the sticker in the urban space is challenged by a similar difficulty of appeal, which makes it seek in the virtual world the opportunity for an extended exposition, even if their visibility is rarefied there as well. Thus, stickers fit well in the present dynamics of those images which, when faced with obstacles to their visibility and their appealing potential (considering the excessive character entailed in their dynamics), are able to redirect themselves to other media, where they end up modifying their visuality and the way they communicate in order to be seen. As for methodological strategies, we shall undertake an analysis of the formation of this specific imagery, an inquiry of the spatialities, temporalities and communicabilities configured in each domain, and how these characteristics affect the different visualities urban and virtual so as to unveil their implicit purposes. For such, our investigation roots its theoretical bases in Hans Belting s Theory of Media Image; Harry Pross and Vilem Flusser s Theory of Media; and Ivan Bystrina s Synthetic Theory of Culture all of them having been studied and divulged by Norval Baitello Junior. These theoretical frameworks are supposed to contribute to the comprehension of a phenomenon that displays so many significant variations in its constitution. Our research also takes into consideration James Hillman s concept of Anima Mundi and Marc Augé s concept of Non-Places; Lucrécia Ferrara s readings on visuality/visibility, communicability, temporality and spatiality; Rose de Melo Rocha s studies and exhibitions on Urban Images, Jean Baudrillard s studies on simulacra; Cyberculture by Paul Virilio and Eugênio Trivinho, among others who have collaborated in reading the urban and the cyberspace